Development of Glasgow Coma and Outcome Scales - Jennett, Bryan (Nepal Journal of Neuroscience, 2005)
These scales were developed primarily to facilitate the assessment and recording of initial severity of brain dysfunction and of ultimate outcome in a multicenter study of outcome after severe brain damage. The aim was to use simple terms that could be readily understood by a wide range of observers, including doctors, nurses and others. Repeated observations of the coma scale displayed on a bedside chart give it a second use - the monitoring of improvement or deterioration in conscious level as an indication of recovery or of complications. Early sedation and ventilation can make assessment difficult but the motor score alone is still a good guide to severity. Giving numbers to the level of response in the three components of the coma scale (eye opening, motor and verbal responses) facilitates communication between different staff, including those consulted by telephone. Adding up these scores to give an overall coma score (from 3 to 15) results in some loss of information but is useful for triage and for epidemiological studies. Even among mild injuries (coma score 13-15) the score discriminates between those more or less likely to develop complications. The outcome scale describes overall social function rather than neurological deficits, and is useful in monitoring recovery. The outcomes so described at six months after injury correlate well with the early coma scale scores, which are therefore useful predictors of likely outcome. Nepal Journal of Neuroscience, Volume 2, Number 1, 2005, Page: 24-28